2018
DOI: 10.20448/journal.509.2018.52.110.117
|View full text |Cite
|
Sign up to set email alerts
|

Opinions of Science Teachers for Classroom Management

Abstract: This study investigates science teachers' concerns about how to achieve effective classroom management, with particular reference to classroom communication, student motivation, physical environments and unwanted student behaviors. A qualitative research method is used in this research. The semi-structured interview form is developed by the researchers as a data collection tool. The study group consists of fourteen science teachers who are working in Mugla province of Turkey, in the academic year of 2015-2016.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 3 publications
(3 reference statements)
1
12
0
Order By: Relevance
“…The complex types of knowledge and related cognitive processes can be expressed in the form of a table, enabling instructors to identify disproportionalities and make improvements through the relationship between the learning objectives and related domains [19] [29] The taxonomy table is useful in enhancing instructors' understanding of the curriculum, lesson planning, and the design of consistent evaluation protocols, thereby ultimately improving the quality of the teaching. In the revised version of Bloom's taxonomy of educational objectives by Anderson [20], [30], the rows and columns each represent knowledge dimensions and cognitive processes, and the cells in the table are intersections between the knowledge dimensions and cognitive processes ( Table 1). All objectives can be classified using this table, and placed in the appropriate cells [21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The complex types of knowledge and related cognitive processes can be expressed in the form of a table, enabling instructors to identify disproportionalities and make improvements through the relationship between the learning objectives and related domains [19] [29] The taxonomy table is useful in enhancing instructors' understanding of the curriculum, lesson planning, and the design of consistent evaluation protocols, thereby ultimately improving the quality of the teaching. In the revised version of Bloom's taxonomy of educational objectives by Anderson [20], [30], the rows and columns each represent knowledge dimensions and cognitive processes, and the cells in the table are intersections between the knowledge dimensions and cognitive processes ( Table 1). All objectives can be classified using this table, and placed in the appropriate cells [21].…”
Section: Methodsmentioning
confidence: 99%
“…Another criticism is that Bloom's original taxonomy cannot fully reflect today's logical, experiential knowledge system [11]. Anderson et al addressed the aforementioned issues by modifying Bloom's taxonomy to consider creativity and meta-cognitive knowledge, thereby adopting a dual structure comprising cognitive processes knowledge dimensions [20]. Similar to Table 1, Figure 1 classifies the educational objectives into cognitive processes and knowledge dimensions.…”
Section: Changes In Robotics-related Educational Objectives In Elemenmentioning
confidence: 99%
“…Research framework of this study Studies have shown that task transparency prevents corruption and unethical behaviour among the officers in the public sector. In most countries, the government requires transparency and fairness to combat unethical behaviour among the officers (Cunningham & Darling, 2016;Kubat & Dedebali 2018). The implementation of transparency will reduce corruption and unethical behaviour among the public officers as they need to report all their activities to the public (De Vries & Sobis, 2016).…”
Section: Religiosity and Ethical Behaviourmentioning
confidence: 99%
“…We reported on a case study to uncover the phenomenon since this approach caters to a wide array of portrayals of the participants' voices, agencies, and enactment in their classroom management discourses. In relation to this, scholars have recently explored how classroom management is geared by teachers (see, for example, Egeberg, Mcconney, & Price, 2016;Eisenman, Edwards, & Cushman, 2015;George, Sakirudeen, & Sunday, 2017;Jalali & Panahzade, 2014;Kubat, 2018;Liu & Babchuk, 2018;Selcuk, Kadi, Yildirim, & Celebi, 2017). The results have informed uniform findings that classroom management is essential for teacher-student interactions and negotiations (Dikmenli & Çifç, 2016).…”
Section: Introductionmentioning
confidence: 99%